ANALYSIS OF STRUCTURE AND LANGUAGE ELEMENTS OF FANTASY TEXTS OF CLASS VII STUDENTS OF SMP 4 SOLOK CITY - Putri, Mega (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
ABSTRACT This research is motivated by the language skills that students must master in their learning. One of them is the skill of writing fantasy texts. Learning to write, especially writing fantasy stories, is a skill that aims to tell, describe, or imagine various actions, experiences, and events in the form of wishful thinking, fantasy, imagination, and mere fiction. The aim of this research is to analyze students' fantasy text writing skills which include (1) the structure of a fantasy story consisting of orientation, complication and resolution and (2) the linguistic elements of fantasy consisting of the use of personal pronouns, the use of time sequence conjunctions, the use of words/phrases surprise, and the use of direct dialogue/sentences in the story. The object of this research is the text structure and linguistic elements in fantasy texts created by students. This type of research is descriptive qualitative using descriptive methods. The results obtained in this research were 24 students writing texts, but only 17 of them could be categorized as fantasy texts. From the 17 samples analyzed, it can be concluded that students have been able to write a good fantasy story structure consisting of 17 data orientations, 17 data complications and 17 data resolutions; and the use of personal pronouns is 282 data, the use of time sequence conjunctions is 72 data, the use of words/expressions of surprise is 25 data, and the use of dialogue/direct sentences in stories is 68 data.